Clinicopathological characteristics and outcomes of synchronous renal cell carcinoma and urothelial carcinoma: A population-based analysis - Kan Wu; Xu Liu; Yaohui Wang; Xianding Wang; Xiang Li (Frontiers in Public Health, 2022)
BackgroundTo better understand the characteristics, and survival outcomes of synchronous renal cell carcinoma (RCC) and urothelial carcinoma (UC), we described and analyzed the clinical features, factors, and prognosis of patients with synchronous RCC and UC using a large population-based database.MethodsWithin the Surveillance, Epidemiology, and End Results (SEER) database (2004–2016), we identified patient with concurrent RCC and UC at initial diagnosis. Their clinicopathological features and prognosis were evaluated. A logistic regression model was used to examine risk factors for the occurrence of concomitant RCC and UC, and Kaplan-Meier survival curves were used to estimate overall survival.ResultsA total of 61,454 RCC patients were identified from the SEER database, 704 (1.1%) patients presented with synchronous RCC and UC. Among these patients, concurrent bladder tumors (566/704) are more common. Subsequently, subgroup analysis based on the location of UC indicated that patients with concurrent RCC and upper tract urothelial carcinoma (UTUC) had unfavorable UC characteristics (higher tumor stage and grade), compared with patients with concomitant bladder cancer. An increased risk of concurrent UC was observed among older age, male sex, and white race. Meanwhile, papillary RCC histology [odds ratio (OR) 3.23; 95% confidence interval (CI) 2.13–4.90], and smaller tumor (OR 6.63; 95% CI 4.46–9.87) were independent risk factors for concomitant UTUC. In addition, we found that synchronous RCC and UTUC was associated with worse survival by using Kaplan-Meier and multivariable analysis [hazard ratio (HR) 2.36, 95% CI 1.89–2.95]. However, concomitant bladder cancer did not affect survival outcomes of patients with RCC (HR 1.00, 95% CI 0.86–1.17).ConclusionWe found that synchronous concurrent RCC and UC is relatively uncommon and mostly located in the bladder. Older age, male sex, and white race increase the risk of synchronous RCC and UC. Meanwhile, patients with papillary RCC histology, and smaller tumors are more likely to have concomitant RCC and UTUC. Furthermore, our findings suggest that synchronous RCC and UTUC has a worse prognosis, while, concomitant bladder tumor did not affect the oncological outcomes of RCC.